Signal partitioning in superfluid 4He: a Monte Carlo approach - Toschi, Francesco; Brunold, Axel; Burmeister, Lea; Eitel, Klaus; Enss, Christian; Fascione, Eleanor; Ferber, Torben; Gabriel, Rahel; Hauswald, Lena; Kahlhoefer, Felix; Kempf, Sebastian; Klute, Markus; et al. (Physical review, 2025)
Superfluid 4He is an ideal candidate for the direct detection of light dark matter via nuclear recoils thanks to its low nuclear mass and the possibility to reach a low-detection-energy threshold by exploiting the generated quasiparticles. The design of future detectors based on this target, such as the DELight experiment, requires a proper understanding of the formation and partitioning of the signal for different energy depositions from various sources. This work presents an overview of the physical processes involved in the energy deposition of recoiling electrons and ions, and it describes a Monte Carlo approach to the partitioning of the signal into different channels. Despite an overall good agreement with existing literature, differences in the region of interest for light dark matter searches below 200 eV are observed.
Die 4 im Titel ist hochgestellt
Online veröffentlicht: 24. Februar 2025
Gesehen am 22.10.2025